ENHANCING SCHOOLS – INDUSTRIES PARTNERSHIP IN SCIENCE EDUCATION: IMPLICATIONS FOR NIGERIAN SECONDARY SCHOOLS - Ojimba, Daso Peter (European Scientific Journal, ESJ, 2013)
The rate at which scientific knowledge explode and the pace at which technology is rapidly changing demands much more than school science to catch up with industrial processes. The present parallel nature of school science and industries does increase the wide gap between modern day reality and out of date school science. To bridge the gap between school science and industries, cooperation between the two as partners must be developed and given the sanctity of curriculum approval. The benefits of this partnership are enormous: students acquire industrial skills, develop work habit, instill positive attitude in students towards industries etc. However, the paper discussed the model of school – industries relationship, need for curriculum reform for Nigerian science education, hindrances to schools – industries partnership. However, to harmonise science education as practiced in Nigerian secondary schools with industrial process, some recommendations were made.